Calcium modified basalt fiber bio-carrier for wastewater treatment: Investigation on bacterial community and nitrogen removal enhancement of bio-nest. (September 2021) - Gao, Fengyi; Zhou, Xiangtong; Ma, Yuting; Zhang, Xiaoying; Rong, Xinshan; Xiao, Xiang; Wu, Zhiren; Wei, Jing
Graphical abstract: Highlights: Calcium modified basalt fiber carriers with improved bio-affinity were developed. Bacterial adhesion, biomass and EPS immobilization were enhanced on Ca-MBF. Increased abundance of nitrifiers and denitrifiers in bio-nest formed on Ca-MBF. Modified carrier had higher COD and nitrogen removal rates in long-term test. Stable nitrogen removal performance was showed by calcium modified carrier. Abstract: Modified basalt fiber (MBF) is a sustainable material studied as novel wastewater treatment bio-carrier recently. This work studied the effects of calcium modification on the bacterial affinity of modified fiber (Ca-MBF), bacterial community, and nitrogen removal performance. Results showed that Ca-MBF with hydrophilic (62.66°) and positively-charged (7.80 mV) surface accelerated bacterial attachment. Volatile suspended solids on Ca-MBF (5.46 g VSS/g fiber) were increased by 2.61 times after modification, with high bacterial activity when bio-carriers were cultured in activated sludge. Extracellular polymeric substances on Ca-MBF was 4.35 times higher and consisted of more protein. Bio-nests with unique aerobic/anaerobic structure formed on the ultrafine carriers in bioreactor. Ca-MBF bioreactor exhibited total nitrogen removal efficiency above 72.2% and COD removal efficiency above 94.2% with more stable performance than unmodified carrier in long-term treatment using synthetic domestic wastewater.16S rRNA gene sequencing revealed enhanced abundance of nitrifying and denitrifying bacteria in Ca-MBF bio-nest.